PENGUATAN KAPASITAS PRODUKSI DAN MANAJEMEN USAHA BERBASIS KOMUNITAS MELALUI PEMBERDAYAAN KELOMPOK USAHA BERSAMA - Julita, Julita; Iznillah, Muhammad Luthfi; Karina Andini, Frini; Diah Septia Ningrum; Raja Abelda Gusnawati; Fatimah Azzahra (Jurnal Abdi Insani, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role as drivers of rural economic growth and pillars of community welfare. However, many MSMEs still face fundamental challenges in production processes and business management. KUBE Berkah Abadi in Kuapan Village, Kampar Regency, is one example of a potential MSME producing Dendeng Pucuk Ubi (cassava leaf jerky), but it still requires technological intervention and strengthened management capacity. Therefore, a targeted empowerment program is needed to enhance the competitiveness and independence of the business unit. This activity aims to improve the production capacity and business management of KUBE Berkah Abadi through the provision of appropriate technology, the development of Standard Operating Procedures (SOPs) for production, comprehensive training, and continuous field assistance. The program was carried out using a participatory approach through stages of problem identification, priority setting, solution design, field implementation, and systematic monitoring and evaluation. The results show that the partner group has received and actively utilized simple production equipment to increase work efficiency. Production SOPs have been developed and implemented to maintain product quality standards. Comprehensive training on business management, financial recording, digital marketing, and business legality ran effectively, as evidenced by the significant improvement in participants' post-test scores. The partner has begun applying simple financial records, and short- and medium-term business work plans have been prepared together with the facilitation team. Intensive assistance has supported partners in daily operational practices and marketing strategies. This program has proven effective in enhancing production capacity, management quality, and entrepreneurial motivation, thereby contributing to the sustainability and self-reliance of the business.